Implementasi Model Kepemimpinan Kontingensi dalam Pengembangan Lembaga Pendidikan Islam - Arfandi Arfandi; Muhammad Ihwan (Jurnal Pendidikan Islam Indonesia, 2020)
The implementation of the contingency leadership model in the development of Islamic education institutions is one of the platforms for the fulfillment of effective and efficient Islamic education with a variety of infrastructure, regulations, and a sense of responsibility. Contingency leadership is a leadership model explaining that a leader can be effective when the leader style and the leader situation are convenient. Contingency theory assumes that leadership is the process of exercising an influence related to the group task situation.